2013
DOI: 10.1371/journal.pone.0083598
|View full text |Cite
|
Sign up to set email alerts
|

Risk Taking in Hospitalized Patients with Acute and Severe Traumatic Brain Injury

Abstract: Rehabilitation can improve cognitive deficits observed in patients with traumatic brain injury (TBI). However, despite rehabilitation, the ability of making a choice often remains impaired. Risk taking is a daily activity involving numerous cognitive processes subserved by a complex neural network. In this work we investigated risk taking using the Balloon Analogue Risk Task (BART) in patients with acute TBI and healthy controls. We hypothesized that individuals with TBI will take less risk at the BART as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This could also indicate a deficit in risk-assessment, or an increase in risk-taking behavior. Clinical studies have demonstrated increased impulsivity, compulsive behaviors, addiction, careless or violent behavior and suicide, in patients with moderate to severe injury (Greve et al, 2001, Grados et al, 2008, Noggle and Pierson, 2010, Fecteau et al, 2013, James et al, 2014, Juengst et al, 2014), consistent with deficits in risk-assessment. We conclude that post-injury increase in exploration of the exposed zones by vulnerable animals represents a maladaptive anxiety state.…”
Section: Discussionmentioning
confidence: 97%
“…This could also indicate a deficit in risk-assessment, or an increase in risk-taking behavior. Clinical studies have demonstrated increased impulsivity, compulsive behaviors, addiction, careless or violent behavior and suicide, in patients with moderate to severe injury (Greve et al, 2001, Grados et al, 2008, Noggle and Pierson, 2010, Fecteau et al, 2013, James et al, 2014, Juengst et al, 2014), consistent with deficits in risk-assessment. We conclude that post-injury increase in exploration of the exposed zones by vulnerable animals represents a maladaptive anxiety state.…”
Section: Discussionmentioning
confidence: 97%
“…64 Patients with traumatic brain injury also seem to display abnormally cautious risk taking as shown, for instance, in the Balloon Analog Risk Task. 65 Again, further investigations are needed to better describe impaired and intact decisionmaking skills and its associated neural substrates in these populations.…”
Section: Othermentioning
confidence: 99%
“…People with neurodevelopment disorders (NDD) such as autism, intellectual learning disability and attention deficit disorders; brain degenerative disorders (BDD) such as Alzheimer disease and other degenerative diseases of the nervous system; or traumatic brain injuries (TBI), have a high disease burden due in part to impaired brain functioning, experience challenges in their life situations, and require urgent clinical care at times (Fecteau et al . ; Garvin & Mangat ; Ghroubi et al . ; Gutierrez et al .…”
Section: Introductionmentioning
confidence: 99%
“…People with neurodevelopment disorders (NDD) such as autism, intellectual learning disability and attention deficit disorders; brain degenerative disorders (BDD) such as Alzheimer disease and other degenerative diseases of the nervous system; or traumatic brain injuries (TBI), have a high disease burden due in part to impaired brain functioning, experience challenges in their life situations, and require urgent clinical care at times (Fecteau et al 2013;Garvin & Mangat 2017;Ghroubi et al 2016;Gutierrez et al 2008;Howe 2008;Kopecky et al 2013). Most of these patients experience neuropsychiatric symptoms such as depression and anxiety (Garvin & Mangat 2017;Howe 2008;Kopecky et al 2013), as well as impaired self-efficacy (Ownsworth et al 2010;Ponsford et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation